Overuse of Diagnostic Tests in Canada: A Critical Perspective - Borges, Julia; Lee, Tiffany; Saif, Abdullah; Sundly, Amit; Brunger, Fern (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2019)
In this commentary we describe the interplay between 1) contemporary popular and professional understandings of “risk” and “normality” in health and healthcare, and 2) the promotion by state and market forces of individual self-regulation of health. We draw upon the work of critical theorists who have described the relationship between risk, fear, and the notion of “normal” in health discourse to argue that these factors act, primarily via the popular media, to shape the discourse on, and overuse of, diagnostic tests in Canada.